Games Without Frontiers? Socio-historical Perspectives at the Gaming/Gambling Intersection - Wardle, Heather (Leisure Studies in a Global Era, 2021)
This open access book focuses on how and why digital games and gambling are increasingly intertwined and asks "does this matter?" Looking at how "loot boxes" became the poster child for the convergence of gambling and gaming, Wardle traces how we got here. She argues that the intersection between gambling and gaming cultures has a long lineage, one that can be traced back throughout the 20th century but also incorporates more recent trends like the poker boom of the 1990s, the development of social media gambling products and the development of skin betting markets. Underpinned by changing technology, which facilitated new ways to bet, trade and play, the intersection between gaming and gambling cultures and products has accelerated within the last decade - and shows little signs of stopping. Wardle explores what this means for our understanding of risk, how gaming and gambling entities use each other for commercial advantage, and crucially explores what young people think of this, before making recommendations for action.